High Expression of Integrin α3 Predicts Poor Prognosis and Promotes Tumor Metastasis and Angiogenesis by Activating the c-Src/Extracellular Signal-Regulated Protein Kinase/Focal Adhesion Kinase Signaling Pathway in Cervical Cancer - Du, Qiqiao; Wang, Wei; Liu, Tianyu; Shang, Chunliang; Huang, Jiaming; Liao, Yuandong; Qin, Shuhang; Chen, Yili; Liu, Pan; Liu, Junxiu; Yao, Shuzhong (Frontiers in Oncology, 2020)
Background: Cervical cancer remains a leading cause of death in women due to metastasis to distant tissues and organs. Integrins are involved in cancer metastasis. However, whether integrin α3 participates in cervical cancer metastasis is under investigation. In this study, we explored the effect and detailed mechanism through which integrin α3 regulates cervical cell migration, invasion, and angiogenesis. Methods: Firstly, we explored the mRNA and protein expression levels of integrin α3 in cervical cancer cell lines and tissue samples obtained from patients. After knocking down the expression of integrin α3 using shRNA, the proliferation, migration, and invasion of cervical cancer cells, as well as the possible signaling pathways involved, were investigated in vitro. In addition, tube formation, proliferation, and migration of human umbilical vein endothelial cells were tested to identify their effect on angiogenesis. Zebrafish tumor migration and nude mouse lung metastasis models were utilized for the in vivo analysis. Results: We examined samples from 142 patients with cervical cancer and 20 normal cervixes. Integrin α3 was highly expressed in patients and predicted poor overall survival and disease-free survival. In SiHa cells, treatment with integrin α3 shRNA induced the phosphorylation of protein focal adhesion kinase and enhanced focal adhesion. These events were mediated by the activation of c-Src and extracellular regulated protein kinase cascades. Consequently, integrin α3 increased the migratory ability of SiHa cells. In addition, knockdown of integrin α3 decreased the tube formation, proliferation, and migration of human umbilical vein endothelial cells, as well as the levels of matrix metalloproteinase-9, indicating its effect on angiogenesis. Stable transfection with integrin α3 shRNA reduced the migratory ability of SiHa cells in the zebrafish model and diminished lung metastasis in the xenograft mouse model. Conclusion: Integrin α3 recruits the c-Src/extracellular regulated protein kinase cascade, leading to phosphorylation of focal adhesion kinase. Moreover, it regulates focal adhesion, endowing cervical cancer cells with potentiated migratory and invasive ability and promotes angiogenesis via matrix metalloproteinase-9. Our findings may shed light on the mechanism involved in cervical cancer metastasis and highlight integrin α3 as a candidate prognostic biomarker and therapeutic target in patients with cervical cancer.